European NUTS 2 regions: construction of interregional trade-linked Supply and Use tables with consistent transport flows - Mark Thissen; Olga Ivanova; Giovanni Mandras; Trond Husby (European Commission, Joint Research Centre (JRC), 2019)
Economic development is interregional in nature, with economic growth being determined by physical and technological proximity identified by interregional and national cross-border interactions in trade, investments, and knowledge. This report explains the construction of a system of multiregional input-output tables for the EU28 interlinked with trade in goods and services within the same country as well as with regions in other Member States. Taking transhipment locations into account, trade in goods and services is derived from freight transport data, airline data on flights, and business travel data. The methodology is centred on the probability of trade flows and was developed to fit the information available without pre-imposing any geographical structure on the data.
Keywords: C67; C82; D57; R15; 330; rhomolo; region; growth; NUTS 2 regions; national accounts; Supply/Use tables; Input-output tables; inter-regional trade